2008
DOI: 10.1353/rhe.2007.0077
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and Pedagogy: Faculty's Spirituality and Use of Student-Centered Approaches to Undergraduate Teaching

Abstract: Using data from a national survey of college faculty, this study examines faculty members' preferred teaching practices as one aspect of their professional behavior that may reflect the spiritual dimension of their own lives. Findings show that faculty who are highly spiritual are more likely than their less spiritual colleagues to use student-centered pedagogy. The results have implications both for enhancing understanding of pedagogical practice and addressing faculty personal and professional development is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…As pointed out earlier, most early research into spirituality in academia focused on student spirituality (Lindholm & Astin, 2008). Nonetheless, research that has focused on the faculty is emerging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As pointed out earlier, most early research into spirituality in academia focused on student spirituality (Lindholm & Astin, 2008). Nonetheless, research that has focused on the faculty is emerging.…”
Section: Discussionmentioning
confidence: 99%
“…Shahjahan (2010) studied the role of spirituality among faculty of color teaching for social justice. Lindholm and Astin (2008) investigated faculty spirituality and the use of student-centered approaches to undergraduate teaching. Tolliver and Tisdell (2006) Some studies have found gender-based distinctions concerning personal spirituality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The situation is similar with approaches to faculty development, most of which concern themselves with scholarship, teaching evaluations, and service to the institution without regard to the hopes, fears, and frustrations of faculty members (Lindholm, Astin, and Astin, 2005;Astin, 2004 and sense of community within this structure. Is it any wonder that despite the efforts of faculty development centers, faculty discontent is growing?…”
Section: Spirituality and Higher Educationmentioning
confidence: 94%
“…This view values personal development yet also suggests a need to move beyond the personal and into influencing the world through social justice initiatives. Spiritual development is an integral part of our development as human beings and should be considered in faculty and student lives (Lindholm and Astin 2008). One of the ways Naropa is unique is how it values the spiritual paths of employees.…”
Section: Spirituality In Higher Educationmentioning
confidence: 99%